The Impact of Telehealth on Clinical Education in Adolescent Medicine During the COVID-19 Pandemic: Positive Preliminary Findings - Pham, Do-Quyen; Golub, Sarah A.; Breuner, Cora Collette; Evans, Yolanda N. (Frontiers in Pediatrics, 2021)
Purpose: Following the start of the COVID-19 pandemic, much of clinical care rapidly transitioned to telehealth, shifting the clinical training milieu for most trainees. In the wake of this shift, educators have attempted to keep learners engaged in patient care and optimize medical education as much as possible. There is, however, limited understanding of the effect of telehealth on clinical education. The aim of our study was to better understand the educational experience of pediatric and Adolescent Medicine trainees participating in clinical encounters via telehealth in a specialty consultation Adolescent Medicine Clinic at a quaternary pediatric care hospital. Methods: Using a web-based anonymous questionnaire, we surveyed trainees rotating through the Adolescent Medicine Clinic between March and June 2020. We used descriptive statistics to evaluate their experiences with telehealth and identify techniques that were effective to facilitate learning during a telehealth visit. Results: Surveys from 12 pediatric and Adolescent Medicine trainees were received, a 75% response rate. Most trainees (83.3%) reported no prior experience with telehealth before the onset of the pandemic. By the end of their rotation, trainees identified techniques that helped facilitate learning during a telehealth visit. The majority of trainees (83.3%) rated their experience as effective or very effective, and all reported interest in incorporating telehealth into their future practice. Conclusions: Pediatric and Adolescent Medicine trainees reported overall positive experiences with telehealth in clinical education and an interest in incorporating this tool into future practice. Additional research is needed to refine techniques in engaging learners through telehealth.